An associative study of the ribosomal protein genes, rps3 and rps2 with the p53 tumour suppressor gene - Ting, Chee Enn (Universiti Malaysia Sarawak (UNIMAS), 2013)
Ribosomal proteins (RP) are canonically associated with ribosome biogenesis. However, ribosomal protein small subunit 3 (RPS3) is also known for its DNA repair and apoptosis inducing ability whereas ribosomal protein small subunit 12 (RPSI2) is recognized for its RNA splicing and modification functions. Furthermore, RPS3 was found to interact with a tumour suppressor gene, p53 through its KH domain. However, there has been no literature to date on the association between RPSI2 and p53. In addition, RPS3 and RPSI2 have been found to be associated to a number of cancer types although studies in nasopharyngeal carcinoma (NPC) have not been fully undertaken. In this study, correlative expression patterns of RPS3 and RPSI2 to p53 was studied in nasopharyngeal cell lines. Correlation of RPS3 and RPSI2 was also studied in normal and NPC cell lines. This was done using reverse transcriptase PCR (RTPCR) for transcript analysis. This study revealed specific PCR products with estimated size of l72bp, 741bp and 1306bp for RPSI2, RPS3 andp53 respectively. RPS3 and RPSI2 were found to be significantly down-regulated (p < 0.05) in HKl cell line suggesting association of these genes with well-differentiated nasopharyngeal carcinoma. On the other hand, no significant correlation (p > 0.05) was found between RPS3 and p53; RPSI2 and p53 and also between RPS3 and RPSI2 in all NPC and normal NP69 cell lines.